Knowledge and personal values on fertility preservation procedures in Korean women - Eun Mi Lee; Jieun Jang; Jaekyung Bae; Uisuk Kim; Sokbom Kang (PLoS ONE, 2025)
This study aimed to identify the knowledge of young general Korean female population on reproductive aging, as well as to investigate the personal values regarding fertility preservation (FP). A cross-sectional online survey study of 500 Korean female population on reproductive aging (18–40 years old) was performed. Knowledge regarding fertility preservation and its procedures was generally low. Correct knowledge about FP procedures was less than 50% for most of the questions. The rate of incorrect answers regarding FP knowledge overpassed 50%, which were related to loss of fertility and birth defects due to cancer treatment, and the rate of successful pregnancy for egg and embryo freezing. We also identified the personal values that influenced the willingness of women to undergo FP procedures. These included the following: 1) pregnancy success rate; 2) side effects of FP procedures; 3) delay of cancer treatment due to FP procedure; 4) risk of cancer recurrence; and 5) medical costs of FP procedures. Over 80% of the participants considered all five values important, with almost no distinctions. Despite the general awareness of FP, this study highlights the lack of knowledge and significant misconceptions regarding FP relative to fertility and cancer treatment among Korean women, which should be addressed properly with targeted education. Additionally, this study demonstrates diverse personal values participants hold regarding FP and the desire their values to be respected during the decision-making process of FP procedure facilitating shared decision-making (SDM).